1993
DOI: 10.1002/cne.903320404
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopic analysis of the rod pathway of the rat retina

Abstract: Two immunocytochemical markers were used to label the rod pathway of the rat retina. Rod bipolar cells were stained with antibodies against protein kinase C and AII-amacrine cells with antibodies against parvalbumin. The synaptic circuitry of rod bipolars in the inner plexiform layer (IPL) was studied. Rod bipolar cells make approximately 15 ribbon synapses (dyads) in the IPL. Both postsynaptic members of the dyads are amacrine cells; one is usually the process of an AII-amacrine cell and the other one frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
209
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 171 publications
(223 citation statements)
references
References 59 publications
14
209
0
Order By: Relevance
“…Rod bipolar cell axon terminals, identified by the presence of a ribbon and the features of their postsynaptic dyads, were never presynaptic to Y1-immunoreactive processes. This finding suggests that the bipolar cell terminals engaged in synaptic relationships with Y1-immunoreactive amacrine cell processes were ON-and OFF-type cone bipolar cells (Famiglietti and Kolb, 1975;Freed et al, 1987;Chun et al, 1993;Wässle et al, 1995).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 84%
“…Rod bipolar cell axon terminals, identified by the presence of a ribbon and the features of their postsynaptic dyads, were never presynaptic to Y1-immunoreactive processes. This finding suggests that the bipolar cell terminals engaged in synaptic relationships with Y1-immunoreactive amacrine cell processes were ON-and OFF-type cone bipolar cells (Famiglietti and Kolb, 1975;Freed et al, 1987;Chun et al, 1993;Wässle et al, 1995).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 84%
“…These studies defined the AII amacrine cells as such and demonstrated several of their synaptic contacts. The homologous gap junctions are located between arboreal dendrites in the innermost part of the IPL (stratum 5; S5; Chun et al, 1993;Kolb, 1979;Sterling, 1983;Strettoi et al, 1992). The gap junctions have been described as small and symmetric and tend to be located between arboreal dendrites that are postsynaptic to the same rod bipolar axon terminal (Strettoi et al, 1992).…”
Section: Homologous Gap Junctions Between Aii Amacrine Cellsmentioning
confidence: 99%
“…As for the homologous junctions between AII amacrines, the first evidence for electrical synapses between AII amacrines and ON-cone bipolar cells also came from ultrastructural studies in cat retina (Famiglietti and Kolb, 1975;Kolb, 1979;Kolb and Famiglietti 1974), but has since been verified for several other mammalian retinas (Chun et al, 1993;Massey and Mills, 1999b;Tsukamoto et al, 2001;Wässle et al, 1995).…”
Section: Heterologous Gap Junctions Between Aii Amacrines and On-conementioning
confidence: 99%
“…5F ). Whereas at the cone bipolar cell synapses the two postsynaptic elements are preferentially a process of an amacrine cell and a dendrite of a ganglion cell (Dowling and Boycott, 1966), at the rod bipolar cell synapse both postsynaptic elements belong to amacrine cells (Famiglietti and Kolb, 1975;Chun et al, 1993). At the bipolar cell synapses only one of the postsynaptic processes was labeled.…”
Section: Mglur5a Is Localized To Amacrine Cell Processes In the Iplmentioning
confidence: 99%